Variation in morphological traits of a selection of Indonesian winged bean accessions (Psophocarpus tetragonolobus) and its analysis to assess genetic diversity among accessions - Izmi Yulianah; Budi Waluyo; Sumeru Ashari; Kuswanto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yulianah I, Waluyo B, Ashari S, Kuswanto. 2020. Variation in morphological traits of a selection of Indonesian winged bean accessions (Psophocarpus tetragonolobus) and its analysis to assess genetic diversity among accessions. Biodiversitas 21: 2991-3000. In Indonesia, winged bean (Psophocarpus tetragonolobus (L.) DC.) is a traditional vegetable crop grown mainly for its edible green pods. Plant breeding programs aim to produce cultivars with high production and good nutritional qualities. The objective of this present study was to assess genetic diversity among 21 selected Indonesian winged bean lines based on observation of morphological characters. This was the first step in determining an appropriate breeding program for the development of improved vegetable cultivars. Twelve qualitative characters and eight quantitative variables were assessed for each of the 21 lines. Categorical differences among lines were observed in characters such as leaflet, pod and seed shape, pod surface texture, anthocyanin pigmentation of stem, flowers and pods. Several of these characters are useful as genetic markers, and cluster analysis of the 21 lines on the basis of qualitative characters enabled two distinct groupings to be identified. Quantitative variation across line means was also high for several of the quantitative variables (a coefficient of variation > 25% for pod length, number of pods per plant, and total pod weight per plant). Principal component analysis applied to the eight variables accounted for 86% of the total variation in just three components with eigenvalues > 1. On Component 1, the characters number of days to first open flower, pod length and pod weight were closely aligned with total weight of pods per plant. Number of pods per plant was not closely aligned with weight of pods per plant. This study has enabled broad differences between groups of lines to be categorized and has identified particular lines with characteristics that recommend them for inclusion as parents in inheritance studies designed to elucidate the contribution that individual characters make to overall productivity, attractiveness, and nutrition of this useful, high protein, vegetable species.